The Effect of Classroom Interaction on Conversation Performance of EFL Learners in Binjai - Ratih; Fernando De Napoli Marpaung (LPPM STKIP AL MAKSUM, 2020)
The objective of this study was to find out the significant difference before and after the students being treated by classroom interaction strategy in speaking class. The researcher used quantitative method and pre experimental design to analyze research problem. This study was conducted to the second grade students of SMAN 6 Binjai on 21th July until 5th August 2020. The data were collected through a speaking test, the test was consists of expressed argumentative text. Firstly, students had to express their opinions about the phenomenon surrounding without being given treatment. In this test, the researcher gave the topic about social media. Secondly, the students expressed their opinions after treatment. The treatment was the researcher teach the students how to expressing opinion, asking other people’s opinion and saying agreement. The test was given to measure the students’ speaking skill after treatment. The researcher investigated the data and collected the score pre- test and post-test based on the scoring system. In analyzing the data, the researcher calculated the data used t-test, the researcher checked the normality of the data using Liliefors test to find out whether the distribution of data was normal, and so the researcher used t-test to clarify whether or not his hypothesis is accepted. The research findings showed that was a difference before and after the students being treated classroom interaction in speaking class. The result of the data showed that = 8,374 was greater than = 2,924. It proved that the result of post-test was better than the result of pre-test. In order to find out the significance of the improvement between pre-test and post-test, t-test was applied. After having the test of significance, the result of pre-test showed that the average score of pre-test was 67. Whereas, the averages score of post-test were 73. From the data showed, the result of the post-test in speaking test was better than the result of pre-test. From the result, it could be concluded that there are the significance of the improvement from pretest and post-test Keywords: classroom interaction, speaking skill